Enteroviruses from Humans and Great Apes in the Republic of Congo: Recombination within Enterovirus C Serotypes - Inestin Amona; Hacène Medkour; Jean Akiana; Bernard Davoust; Mamadou Lamine Tall; Clio Grimaldier; Celine Gazin; Christine Zandotti; Anthony Levasseur; Bernard La Scola; Didier Raoult; Florence Fenollar; et al. (Microorganisms, 2020)
Enteroviruses (EVs) are viruses of the family Picornaviridae that cause mild to severe infections in humans and in several animal species, including non-human primates (NHPs). We conducted a survey and characterization of enteroviruses circulating between humans and great apes in the Congo. Fecal samples (N = 24) of gorillas and chimpanzees living close to or distant from humans in three Congolese parks were collected, as well as from healthy humans (N = 38) living around and within these parks. Enteroviruses were detected in 29.4% of gorilla and 13.15% of human feces, including wild and human-habituated gorillas, local humans and eco-guards. Two identical strains were isolated from two humans coming from two remote regions. Their genomes were similar and all genes showed their close similarity to coxsackieviruses, except for the 3C, 3D and 5′-UTR regions, where they were most similar to poliovirus 1 and 2, suggesting recombination. Recombination events were found between these strains, poliovirus 1 and 2 and EV-C99. It is possible that the same EV-C species circulated in both humans and apes in different regions in the Congo, which must be confirmed in other investigations. In addition, other studies are needed to further investigate the circulation and genetic diversity of enteroviruses in the great ape population, to draw a definitive conclusion on the different species and types of enteroviruses circulating in the Republic of Congo.